2019
DOI: 10.1111/odi.13103
|View full text |Cite
|
Sign up to set email alerts
|

Association of long non‐coding RNA MEG3 polymorphisms with oral squamous cell carcinoma risk

Abstract: Objective Long non‐coding RNA (lncRNA) MEG3 was associated with multiple types of cancers such as oral squamous cell carcinoma (OSCC). Single nucleotide polymorphisms (SNPs) might affect cancer risk by modifying the function of lncRNAs. But fewer study researched the relationship between SNPs and MEG3 in cancers. Considering these reasons, we supposed SNPs in MEG3 may influence the risk of OSCC. Material and Methods The selected SNPs in MEG3 were genotyped in 1,428 subjects (444 patients with OSCC and 984 canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…For example, in clinical therapy, surgical resection is an effective treatment for localized tumors, but the disease could still exhibit potential regional or distant metastasis, or high resistance toward conventional chemotherapy and radiotherapy. Therefore, researchers have focused on the potential molecular biologi-cal mechanisms of cancer development, such as genetic biomarkers which can be used as prognostic factors for cancer patients [4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in clinical therapy, surgical resection is an effective treatment for localized tumors, but the disease could still exhibit potential regional or distant metastasis, or high resistance toward conventional chemotherapy and radiotherapy. Therefore, researchers have focused on the potential molecular biologi-cal mechanisms of cancer development, such as genetic biomarkers which can be used as prognostic factors for cancer patients [4].…”
Section: Introductionmentioning
confidence: 99%
“…Previous evidences showed that MEG3 was highly expressed in normal tissues such as brain, pituitary, placenta and adrenal gland, and its transcripts can be detected in several human organs including ovary, testes, spleen, pancreas, liver, and mammary gland [7]. However, the expression of MEG3 was lower in various human tumors compared with that in normal human tissues, including breast cancer [24]. MEG3…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported that SNPs in MEG3 gene have an in uence on cancer risk. For example, Hou et al observed a statistically signi cant increased risk between MEG3 rs11160608 and oral squamous cell carcinoma (OSCC) [24]. And Bayarmaa et al found MEG3 polymorphisms were related to the chemotherapy response and toxicity of paclitaxel and cisplatin in breast cancer patients [32].…”
Section: Discussionmentioning
confidence: 99%
“…As the most common type of genetic Previous evidences showed that MEG3 was highly expressed in normal tissues such as brain, pituitary, placenta and adrenal gland, and its transcripts can be detected in several human organs including ovary, testes, spleen, pancreas, liver, and mammary gland [4]. However, the expression of MEG3 was lower in various human tumors compared with that in normal human tissues, including breast cancer [15]. MEG3 was recognized as a tumor suppressor deponed on recent researches.…”
Section: Discussionmentioning
confidence: 99%